The Effect Of Generation X And Generation Y Behavior On Employee Loyalty Through Job Satisfaction - Sunarta, Sunarta; Zainuri, Zainuri (Universitas Muhammadiyah Prof. DR HAMKA., 2019)
This study aims to determine the effect of Generation X and Generation Y behavior on employee loyalty through job satisfaction. The method utilized survey method using quantitative approach with 78 respondents from Generation X and 55 respondents from Generation Y. Chi Square method was used to test the hypothesis of this research. The results of this study have found that there are differences in behavior between Generation X and Generation Y employees in assessing job satisfaction and employee loyalty. The differences in the behavior of Generation X and Generation Y in assessing job satisfaction and loyalty should be put into a serious concern so that the company’s regeneration process can proceed without hindrance for the continuation of a sustainable company life..